New Pre-reacted Glass Containing Dental Composites (giomers) with Improved Fluoride Release and Biocompatibility - Colceriu Burtea, Loredana (Materials (Basel), 2019)
The aim of the present work was to prepare a series of novel restorative giomers and investigate the morphology, the physico-chemical properties (residual monomer, fluoride release), and the cytotoxicity of the new materials. The experimental giomers were prepared as light-cured pastes by blending different resin matrices comprising aromatic/aliphatic/urethane (di) methacrylates, with hybrid fillers containing pre-reacted glasses (PRGs), a radiopaque glass, and nano fluorhydroxyapatite. Polyalkenoic acids based on acrylic acid/itaconic acid/N-acryloyl -L-leucine modified or not with methacrylic groups, together with a superficially active glass, were used to prepare the PRGs. The fluoride ion release of the experimental giomers was investigated within a period of 60 days of storage in bidistilled water while using a fluoride ion selective electrode. Beautifil II commercial product was used as a reference. Cell cytotoxicity tests were done in vitro, in accordance with ISO 10993-122012 proceedings. Human dermal fibroblasts and umbilical endothelial vein cultures were used. The values that were obtained for cumulative fluoride release for all experimental giomers were higher than for the Beautifil II product, being more than twice the ones that were obtained for the commercial product after 60 days of storage in bidistilled water. The experimental biomaterials showed similar and/or better results when compared to the commercial one; this effect was maintained in all tested conditions.